Two Case Reports of Varicocele Rupture during Sexual Intercourse and Review of the Literature. (10th December 2018) - Arif, Chalil; Kotoulas, Konstantinos; Georgellis, Chrysostomos; Frigkas, Konstantinos; Bantis, Athanasios; Patris, Emmanouil
Abstract : Varicocele is characterized by the dilatation of the veins of the spermatic cord. Its prevalence in general male population is 15% while in the infertile population the prevalence rises up to 25%. The varicocele is considered an etiological factor for male infertility. Although different pathophysiological patterns have been proposed, there is no consensus in the urological society to date. In most of the cases varicocele is asymptomatic but sometimes gives mild symptoms as dull pain at the scrotal region. A rare complication of this condition is the spontaneous or traumatic rupture and hematoma formation, either as spermatic cord hematoma or as scrotal hematoma. We are presenting two cases of varicocele rupture, presented with acute painful swelling of the left inguinal and scrotal region during sexual intercourse. Imaging studies revealed a scrotal hematoma in the first case and a spermatic cord hematoma in the second case, without signs of active bleeding. Both patients were treated conservatively and recovered uneventfully. Subsequently, we reviewed the literature in an effort to find the key points for the diagnosis and treatment of this condition.